SISTEM INFORMASI GEOGRAFIS PEMETAAN CAFE, WARUNG MAKAN DAN KEDAI KOPI BERBASIS WEB DI KOTA TEMBILAHAN - Sismai Rita; Usman Usman (JURNAL PERANGKAT LUNAK, 2022)
This was followed by a fast internet network speed that made the geographic information system easy to use by all people, including the mapping process for cafes, food stalls and coffee shops. the system will help to make it easier for consumers to find locations, help to convey information and become a media promotion of cafes, food stalls and coffee shops in Tembilahan. In the system design process, the method chosen as the development method is waterfall and uses object-oriented modeling, namely UML ( Unified Modeling Language) and using the PIECES analysis method in building geographic information systems mapping web-based cafes, food stalls and coffee shops in the city of Tembilahan with this geographic information system making it easier for consumers to get locations and information about cafes, food stalls and coffee shops in Tembilahan. , save consumers time and become a promotional medium for the owner of the culinary place.